Moderating Role Of Inflation In Macroprudential Policy And Banking Risk: Indonesian Sharia Banks - Putri Fariska; Mochamad Malik Akbar Rohandi (Center for Risk Management & Sustainability and RSF Press, 2026)
This paper investigates the moderation effect of macroeconomic policy on the effectiveness of macroprudential and risk management in sharia bank. Macroprudential policies are increasingly being used, developing countries use them the most, especially those related to foreign exchange, but several studies state that this policy will help the country's level of financial stability which will ultimately improve the economy. Apart from that, several countries have revealed that macroprudential policy will be more effectively implemented when the government implements tight monetary policy. We took data from 2010-2024 we try to examine the effect macroprudential to risk management when the government implements tight monetary policy using Moderation Regression Analysis to capture conditional effect and conditional interaction. From this research, we can conclude that hat the implementation of macroprudential policy in sharia banking has a significant influence on risk management through managing financing risk and liquidity risk, while the magnitude of the influence of implementing macroprudential policy on risk management will depend on macroeconomic policy, namely the inflation rate, but only affects liquidity risk management and does not affect financing risk management. Directly, the inflation rate also has an influence on liquidity risk in Islamic banking. In other words, the intermediation function of sharia banking can run optimally due to the effectiveness of implementing macroprudential policies, so that banks are able to carry out their functions well.